National Liberation Movements and Their Impact on State-Building Processes at the Beginning of the 20th Century (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines how state-building initiatives in different nations were impacted by national liberation movements that arose around the start of the 20th century. The fight against colonialism and imperialist policies led to the formation of national liberation groups, whose political, social, and economic facets are taken into account. The impact of movements on state independence, political system construction, and national identity building is examined in this article. At the same time, historical materials are used to assess the outcomes of the movements in other nations.